Analysis of the guiding principles on business and human rights ten years after its creation - Hugo GONZÁLEZ (Communications of International Proceedings, 2023)
The present study aims to analyze the situation of the guiding principles and human rights after 10 years of gestation. An analysis of the discourse of specialists who have participated in various academic meetings has been carried out. It is concluded that the guiding principles are still limited in their compliance by companies and due to the lack of intervention (with effective regulations) of the State. Some companies are unaware of the principles. The action plans on the application of the principles are limited and, on the other hand, they are not binding; for this reason it is required that there is a legal responsibility of the companies. However, some progress can also be seen in Europe, such as France and Germany; also, in some Latin American countries such as Chile and Colombia, who have consolidated their second action plan.
Keywords: guiding principles; human rights; social responsibility; legal responsibility; action plan; standards.